Numerical investigation of magnetic field inclination angle on transient natural convection in an enclosure filled with nanofluid. Issue 7 (30th September 2014) - Kharati Koopaee, Masoud; Jelodari, Iman
Abstract : Purpose: – The objective of present research is to characterize the unsteady thermal behavior of a square enclosure filled with water-Al2 O3 nanofluids in the presence of oriented magnetic fields. The purpose this paper is to study the effect of pertinent parameters on the transient natural convection in the enclosure. Design/methodology/approach: – In this research, an in-house implicit finite volume code based on the SIMPLE algorithm is utilized for numerical calculations. To ensure the accuracy of results, comparisons are also made with previous works in literature. In this study, a constant strength magnetic field is concerned and for Rayleigh numbers of Ra=103, 104 and 105 the effect of magnetic field orientation with respect to the case of zero inclination on the thermal performance of cavity is investigated at Hartmann number range of Ha=15-90. In the present work, the nano-particle volume fractions range from φ =0-0.06. Findings: – Results show that when Rayleigh number is Ra=103, the inclination angle, solid particles and Hartmann number has no effect on the transient behavior. It is shown that during the time advancement to steady condition, the heat transfer rate relative to zero inclination angle, may reach to a maximum value. This relative maximum heat transfer increases as the inclination angle increases and decreases as the solid volume fraction increases. The effect of increase in Hartmann number is to decrease this maximum value at Rayleigh number of Ra=104 and at Rayleigh number of Ra=105, depending on the Hartmann number, this value may increase or decrease. It is also found that an increase in Hartmann number leads to delay the appearance of the relative maximum value of heat transfer. Results show that this maximum value is of more significance at zero solid volume fraction when inclination angle is 90 degrees and Hartmann number is Ha=60. Originality/value: – Limited works could be found in the literature regarding the idea of using nanofluids as the working fluid in an enclosure in the presence of magnetic field. In these works, the steady state thermal behavior of enclosures subjected to fixed magnetic fields is concerned. In the present work, the unsteady thermal behavior is concerned and the effect of magnetic field orientation angles on transient heat transfer performance of the enclosure at different Rayleigh and Hartmann numbers and solid volume fractions is explored.